Drug Combination of Ciprofloxacin and Polymyxin B for the Treatment of Multidrug-Resistant Acinetobacter baumannii Infections: A Drug Pair Limiting the Development of Resistance - Junwei Wang; Marc Stegger; Arshnee Moodley; Mingshi Yang (MDPI AG, 2023)
Polymyxins are considered as last-resort antibiotics to treat infections caused by Acinetobacter baumannii. However, there are increasing reports of resistance in A. baumannii to polymyxins. In this study, inhalable combinational dry powders consisting of ciprofloxacin (CIP) and polymyxin B (PMB) were prepared by spray-drying. The obtained powders were characterized with respect to the particle properties, solid state, in vitro dissolution and in vitro aerosol performance. The antibacterial effect of the combination dry powders against multidrug-resistant A. baumannii was assessed in a time-kill study. Mutants from the time-kill study were further investigated by population analysis profiling, minimum inhibitory concentration testing, and genomic comparisons. Inhalable dry powders consisting of CIP, PMB and their combination showed a fine particle fraction above 30%, an index of robust aerosol performance of inhaled dry powder formulations in the literature. The combination of CIP and PMB exhibited a synergistic antibacterial effect against A. baumannii and suppressed the development of CIP and PMB resistance. Genome analyses revealed only a few genetic differences of 3-6 SNPs between mutants and the progenitor isolate. This study suggests that inhalable spray-dried powders composed of the combination of CIP and PMB is promising for the treatment of respiratory infections caused by A. baumannii, and this combination can enhance the killing efficiency and suppress the development of drug resistance.